Influence of environmental regulations on China's tourism competitiveness: Empirical evidence based on provincial panel data. Issue 3 (5th August 2019) - Peng, Cong; Yuan, Peng
Abstract : Purpose: China intends to enhance its environmental regulations, which will affect many industries, because of the serious environmental pollution that the country faces. This study aims to investigate the influence of environmental regulations on China's provincial tourism competitiveness. Design/methodology/approach: A vertical-and-horizontal scatter degree method is used to construct provincial-level tourism competitiveness and environmental regulation indices in China. Thereafter, a spatial econometric model is established to empirically assess the influence of environmental regulations on China's provincial tourism competitiveness and investigate the spatial spillover effects of environmental regulations. Findings: Environmental regulations and China's provincial tourism competitiveness exhibit a "U"-shaped relationship, mainly because of the indirect effects of environmental regulations (spatial spillover effects). The environmental regulation indices of the majority of the provinces have crossed the turning point. Thus, improving environmental regulations has a positive effect on tourism competitiveness. This effect mainly originates from the positive spatial spillover effects. Social implications: Tourism development plays an important role in promoting economic growth. However, increasing environmental pollution may constrain the development of tourism. Therefore, the possible influence of environmental regulations on tourism development should be understood. Originality/value: At present, no research has explored the influence of environmental regulations on China's tourism competitiveness. The current study considers the nonlinear effects of environmental regulations and investigates their spatial spillover effects.